Energy saving potential of a vacuum-based membrane dehumidifier in a dedicated outdoor air system. (1st January 2021) - Cheon, Seong-Yong; Cho, Hye-Jin; Jeong, Jae-Weon
Highlights: A dedicated outdoor air system based on a vacuum membrane dehumidifier is proposed. The proposed system is compared with existing dedicated outdoor air systems. The proposed system saves 57–89% of the dehumidification load. The proposed system consumes 17.4–56.2% lower energy than the existing systems. Abstract: As a novel energy-conservative ventilation system for buildings, a dedicated outdoor air system (DOAS) assisted by a vacuum-based membrane dehumidifier is proposed, and its energy performance is investigated via detailed energy simulations. The vacuum-based membrane dehumidifier dries the air by an isothermal process, which is difficult to realize in conventional dehumidification systems. The proposed system consists of an enthalpy exchanger, a vacuum-based membrane dehumidifier, and a cooling coil. Its dehumidification performance and operation energy are compared with those of the following conventional DOASs: a DOAS that employs a cooling coil (Reference A) and a DOAS that employs an active desiccant wheel (Reference B). To evaluate the energy performance of the proposed system, the energy consumptions of all the DOASs were estimated by simulation programs (i.e., TRNSYS and EES) with mathematical models. The simulation results indicate that the average coefficient of performance of the DOAS we devised (i.e., 1.34) is lower than that of Reference A (i.e., 2.70) and higher than that of Reference B (i.e., 0.80). However, owing to the isothermal dehumidification process, the latent cooling ratio in the case of the proposed system (i.e., 1.0) is significantly higher than those in the cases of Reference A (i.e., 0.43) and Reference B (i.e., 0.11). Consequently, the annual energy consumption of the proposed system is 17.4% and 56.2% lower than those of Reference A and Reference B, respectively.